Florida Beekeeping Management Calendar - James D. Ellis; Catherine M. Zettel Nalen (EDIS)
ENY156, a 7-page fact sheet by J.D. Ellis and C.M. Zettel Nalen, provides Florida beekeepers a reference for honey bee colony management with specific guidance for region by month, including recommendations for major management considerations and blooming plants. Includes reference. Published by the UF Department of Entomology and Nematology, May 2010.